2021
DOI: 10.1111/phn.12916
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with North Dakota’s smoke‐free law among vape and tobacco specialty shops

Abstract: Objective To determine compliance with North Dakota's smoke‐free law in vape shops and other tobacco specialty shops selling electronic nicotine delivery systems (ENDS) or e‐liquids. Design In this 2019 descriptive study, shops (n = 35) were assessed for compliance with the smoke‐free law by observation of indoor and outdoor areas for smoking or vaping, or evidence of such activity in prohibited areas, and the presence of required no‐smoking signs. Results Only two shops (5.7%) were fully compliant with the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Contrary to prior findings of positive impacts of smoke-free legislation on cigarette use [ 81 , 82 ], one of two adolescent and all adult studies reported that indoor vape-free laws did not result in a statistically significant decline in ENP use. This might imply laxity in local enforcement resulting in poor compliance with vaping restrictions in public places [ 83 ] and people’s tolerance to others’ vaping [ 84 ]. Such contrasting observations can be explained by “stealth vaping,” or discreet vaping in prohibited places.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to prior findings of positive impacts of smoke-free legislation on cigarette use [ 81 , 82 ], one of two adolescent and all adult studies reported that indoor vape-free laws did not result in a statistically significant decline in ENP use. This might imply laxity in local enforcement resulting in poor compliance with vaping restrictions in public places [ 83 ] and people’s tolerance to others’ vaping [ 84 ]. Such contrasting observations can be explained by “stealth vaping,” or discreet vaping in prohibited places.…”
Section: Discussionmentioning
confidence: 99%